VITAMIN D POTENTIAL IN REDUCING BLOOD PRESSURE FOR OBESE GERIATRICS - Abraham, John; Bino, Bino Benjamin; Sahoo, Debananda; Shirsat, Vaishali Ashish; Laitonjam, Jonita Devi (International Journal of Pharma and Bio Sciences, 2026)
Vitamin D deficiency and hypertension are significant global health concerns. Despite extensive research, the role of vitamin D in regulating blood pressure remains ambiguous. This raises questions about whether routine vitamin D testing and supplementation should be integrated into hypertension prevention and management strategies. Recent studies have explored the potential mechanisms linking vitamin D to blood pressure regulation, including its effects on vascular function and inflammation. This article reviews the latest evidence, focusing on research from the past two years, to provide insights into this ongoing scientific debate. Previous reviews on vitamin D and blood pressure have often overlooked the specific impact on older adults with obesity, a high-risk group for hypertension. This review addresses this gap by exploring the potential of vitamin D as an adjunct in managing hypertension in this population, emphasizing recent findings and clinical relevance. This article explores vitamin D's role in blood pressure regulation, focusing on biological mechanisms, including the renin-angiotensin-aldosterone system and endothelial impairment linked to reactive oxygen species. It reviews the studies where blood pressure was analyzed as a secondary result, emphasizing the processes of vitamin D in hypertension regulation. Our review also examines the impact of vitamin D supplementation on blood pressure, offering insights into its therapeutic potential. The review integrates recent findings, providing a comprehensive understanding of vitamin D's impact on hypertension management. This review addresses gaps in earlier studies by focusing specifically on older adults with obesity, a group often neglected in hypertension research. It integrates recent findings on vitamin D's mechanisms and supplementation effects, offering updated, targeted insights to guide current clinical strategies in managing hypertension amidst rising obesity prevalence.